Pact for strengthening of high school in rondonia: (re) thinking the school curriculum in languages territories - Bertotti, Mirian de Oliveira; Simões, Robson Fonseca (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2016)
This text is an initial dip. It aims to put to stage the National Pact for Strengthening of High School in Rondônia, PNEM/RO, a program of continuing education of the federal government. The reflections here treated are an invitation to approach us some research sources, seeking to expand our comprehension on this continuing education policy in the territories of Portuguese Language. But what does this policy for the High School look after? For this discussion, we make use of the follow authors: Pimenta (2002), Sacristán (2000), Garcia (2013) and Candau (2007) who help us to reflect about possibilities of pedagogical-curricular approaches in the Language areas. Without pretension to exhaust the debate, this text considers that is important to deepen the discussions on the curricular components in the language paths, considering the impact in the improvement of conditions to learn and develop in subjects and educators at the final stage of Basic Education.